Improved Nonlinear Nishihara Shear Creep Model with Variable Parameters for Rock-Like Materials - Hang Lin; Xing Zhang; Yixian Wang; Rui Yong; Xiang Fan; Shigui Du; Yanlin Zhao (Advances in Civil Engineering)
Creep property is an important mechanical property of rocks. Given the complexity of rock masses, mechanical parameters change with time in the creep process. In this work, a nonlinear function for describing the time-dependent change of parameters was introduced and an improved variable-parameter nonlinear Nishihara shear creep model of rocks was established. By creating rock-like materials, the mechanical properties of rocks under the shear creep test condition were studied, and the deformation characteristics and long-term shear strength of rocks during creep were analyzed. The material parameters of the model were identified using the creep test results. Comparison of the model’s calculated values and experimental data indicated that the model can describe the creep characteristics of rocks well, thus proving the correctness and rationality of the improved model. During shear creep, the mechanical properties of rocks have an aging effect and show hardening characteristics under low shear stress. Furthermore, according to the fact that Gk of the nonlinear model can characterize the creep deformation resistance, a method to determine the long-term shear strength is proposed.